PERAN PEMERINTAH DESA DALAM PELAYANAN KESEHATAN MASYARAKAT DI DESA SUKAJAYA KECAMATAN CIBITUNG KABUPATEN BEKASI - Ifa Inayati; Siti Nuraini (Governance, 2021)
As a legal community unit, the village has the power to regulate and manage its own household, including in realizing health services to improve the quality of health in the community. In health services, it is driven by several sub-systems, such as services for pregnant women, infant health, children and others. The linkage between these sub-systems is interesting to study because changes in one sub-system will have an impact on other sub-systems of the system as a whole. The study is increasingly interesting because in the case of health services, it is still not optimal. This study was conducted to analyze the quality of public health services in Sukajaya village in 2020. With such a goal, the research approach used was qualitative research and data collection techniques through interviews, documentation, and observation. The results show that the sub-systems in health services in Sukajaya village can work and support each other. This can be seen from the implementation of several health service programs in accordance with the regulations set by the state so that in general public health can run well.